Vascular Injury and Its Management: Experience at Universal College of Medical Sciences, Bhairahawa, Nepal - Shah, Santosh; Poudel, Rajesh; Bhandari, Tika Ram; Shah, Damber Bikram; Sigdel, Ghanshyam; Chandra, Kailash (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Vascular trauma is a common life-threatening injury leading to serious consequences if not timely and efficiently managed. Although they represent less than 3% of all injuries, they deserve special attention because of their severe complications. The aim of this study was to analyze the causes of injury, presentations, surgical (recent) approaches, outcomes, and complications of vascular trauma. MATERIALS & METHODS: This was a retrospective analysis performed over 6 months. From December 2015 to May 2016, 12 patients were included in the study and were operated upon for peripheral vascular injuries. Diagnosis was made by physical examination as well as with hand Doppler alone or in combination with Doppler scan. Primary vascular repair was carried out whenever possible; however, if it was not possible, an interposition vein graft was placed. RESULTS: Of the total 12 patients who sustained major vascular injuries during this period, 9 sustained injuries to the upper limb vessels, 3 had injuries of the lower limb vessels. Trauma with sharp object was the cause in 4 cases, blunt trauma was the cause in 4 cases and rupture pesudoaneurysm was the cause in 2 cases and ruptured aneurysm was the cause in 2 cases. Of the 12 patients, 12 patients were successfully managed by vascular reconstruction without any residual disability. There were 8 male patients (66.67%) and 4 female patients (33.33%), and their ages ranged from 16–60 years (mean 35 years). CONCLUSION: Patients who suffer vascular injuries should be transferred to vascular surgery centers as soon as possible. Decisive management of peripheral vascular trauma will maximize patient survival and limb salvage. Priorities must be established in the management of associated injuries, and delay must be avoided when ischemic changes are present. Journal of Universal College of Medical Sciences (2017) Vol.05 No.01 Issue 15, Page: 8-11